The new beauty = Uusi kauneus - Valjakka, Timo 1953- (Siltala Publishing, 2021)
The Norwegian Nicolai Tangen's collection of Nordic modernism is the world's largest in private ownership. Its main focus is on abstract art from after the Second World War, but the arc of the collection extends from the 1920s avantgarde to the 2000s. THE NEW BEAUTY presents works by the collection's Finnish artists, who come together here with their Nordic friends and contemporaries. Among the artists are classic figures such as Sam Vanni and Birger Carlstedt, but also many lesser-known names. The most recent addition to the collection is Elina Brotherus' photographic series Seabound (2018-2019), which she realized at the invitation of the AKO Kunststiftelse for The Tangen Collection. An excerpt of the project is now exhibited for the first time. The Tangen Collection comprises more than 4500 works and is constantly growing. It will get a permanent home in Kristiansand, Norway, when the new Kunstsilo Art Museum opens in 2023. THE NEW BEAUTY has been curated by Timo Valjakka and is being staged in collaboration with the Norwegian AKO Kunststiftelse. The exhibition's visual identity was designed by the architect Hannele Grönlund.
Keywords: Art, Finnish / 20th century / Exhibitions; Art, Finnish / 21st century / Exhibitions; Tangen, Nicolai / Art collections / Exhibitions; Art, Finnish; Art / Private collections; 1900-2099; Exhibition catalogs; Ausstellungskatalog